Reasons for the expansion of inter-municipal health consortia in Pernambuco: perception of state managers - Leal, Eliane Maria Medeiros; Silva, Filipe Santana da; Oliveira, Sydia Rosana de Araujo; Pacheco, Hélder Freire; Santos, Francisco de Assis da Silva; Gurgel Júnior, Garibaldi Dantas (Saúde e Sociedade, 2019)
Intergovernmental cooperation between small municipalities is operationalized through health consortia, historically, in the Brazilian National Health System (SUS). These initiatives favored the decentralization of health in the context of municipalization. However, little is known about its implementation in the regionalization process. The objective of this study was to analyze the reasons for the expansion of intermunicipal health consortia conducted by the state sanitary authority as a new institutional political phenomenon in the regionalization of the SUS in Pernambuco. This is a retrospective analytical study with a qualitative approach. Four semi-structured interviews with state managers were carried out and analyzed using a method of condensation of meanings proposed by Kvale. The Theory of Social Representations guided the data analysis. The reasons for the induction of intermunicipal consortium were: the strengthening of the regionalization of health services; the expansion of supply and co-management of health services; the absorption of successful experiences and the need for state induction of regional health policies. Consortia have become a positive possibility in the perception of state managers in the regionalization of health actions in the state, but additional studies are needed regarding the impact of health indicators on a regional scale.